Kinerja Karyawan Dipengaruh Oleh Knowledge Sharing, Budaya Organisasi, Dan Beban Kerja - Roofelin, Dwivatsih; Korika Swasti, Ika (Jurnal Riset Pendidikan Ekonomi, 2025)
Employee performance is a key factor in supporting service quality within the hospitality industry. Various customer complaints indicate a decline in the quality of services provided. This study aims to analyze employee performance as influenced by knowledge sharing, organizational culture, and workload. The research employs a quantitative approach with a purposive sampling method. The sample consists of 30 employees from one of the hotels in Sidoarjo. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method. The results show that all three independent variables significantly affect employee performance. Knowledge sharing and organizational culture have a positive influence on performance, where higher levels of knowledge exchange and stronger organizational culture lead to better employee outcomes. Conversely, workload has a negative effect on performance, as employees who experience higher workloads tend to demonstrate lower performance levels. These findings emphasize the importance of effective human resource management through enhanced knowledge sharing, strengthened organizational culture, and balanced workload distribution.